The Influence of Individual Resources, Management Support and Human Resource Management on Unit Performance through Corporate Entrepreneurship - Priambodo, Muhammad Aldien (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The intense of disruption in technology make business practitioner have to make decision to maintain their competitive advantage. One of the financial services industry players affected by technological disruption is Bank Mandiri. Bank Mandiri is one of the largest banks in Indonesia, which has to close its branch offices and sub-branch offices. With this in mind, the Corporate Entrepreneurship Strategy must be carried out to maintain competitive advantage and improve high performance. Companies must also be able to exploit existing resources from an external and internal perspective. The focus of this research is to clarify the interaction of individual level resources, in terms of influencing the tendency of companies to obtain resources with the aim of creating corporate entrepreneurship in companies at the level of sub-branch offices or company units. On the other hand, Human Resource Management is also seen as an important factor in corporate entrepreneurship as Management Support did to affects company's internal performance in realizing unit performance improvements. This study uses the Structural Equation Modeling analysis method with the Partial Least Squares approach with the result Management Support and Human Resource Management is in the spotlight as the main supporter and influencer of company performance at the level of sub-branch offices or company units. Improvement in management in terms of supporting the heads of sub-branches and improvements of managing human resources can increase unit performance in order to maintain a competitive advantage in disruption era.